2023
DOI: 10.1530/erc-22-0325
|View full text |Cite
|
Sign up to set email alerts
|

Cell diversity and immune infiltration in the parathyroid tumour microenvironment

Abstract: Tumour microenvironment has been recognized as a crucial factor influencing disease progression. However, relevant features and function are insufficiently understood in parathyroid neoplasia. Single-cell RNA sequencing was performed to profile the transcriptome of 27,251 cells from four parathyroid adenoma (PA) tissue samples. External transcriptomic datasets and immunofluorescence staining of a tissue microarray was set for expression validation. Eight major cell types and various subpopulations were finely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…There is a scarcity of data on PC because of a lack of sufficient amount and preservation of tissue. We performed high-precision scRNA-seq analyses on PC for the first time and compared them with PA, as there have only been two scRNA-seq studies performed on PA samples thus far (28,29) (Table 1). We identified the 11 major cell types described above in parathyroid tumors and revealed significant heterogeneity between parathyroid adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of data on PC because of a lack of sufficient amount and preservation of tissue. We performed high-precision scRNA-seq analyses on PC for the first time and compared them with PA, as there have only been two scRNA-seq studies performed on PA samples thus far (28,29) (Table 1). We identified the 11 major cell types described above in parathyroid tumors and revealed significant heterogeneity between parathyroid adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, CAF is a heterogenous cell population with high plasticity and transformed to a speci c phenotype under distinct TME conditions. Consistent with CAF identi ed in thyroid cancer, colorectal cancer, liver cancer, etc., CAF in parathyroid tumors can be divided into mCAF and iCAF [21,36]. mCAF was characterized by high expression of POSTN, COL1A1, DCN and functioned as extracellular media to promote cancer cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some bulk transcriptomic and proteomic studies have suggested expression signatures of parathyroid chief and oxyphil cells, 5 , 6 , 7 but these studies were based on chief and oxyphil adenoma samples using whole tissue lysates. More recently, a single-cell RNA sequencing (scRNA-seq) study provided an expression atlas of the cell heterogeneity and tumour environment of parathyroid adenomas, 8 but there is still no data available on the normal parathyroid gland.…”
Section: Introductionmentioning
confidence: 99%